Study of Prescribing Pattern and Evaluation of the Efficacy of Monotherapy vs. Polytherapy Antihypertensive Drugs in Diabetes Patients: Pharmaceutical Sciences-Pharmacy Practice - Aghili, Mina; H.S., Shekar (International Journal of Life Science and Pharma Research, 2021)
The monitoring pattern of antihypertensive drugs and evaluation of the efficacy of prescribed pharmacological regimen can provide important vision into control of hypertension and prevention of related comorbidities. This study aimed to evaluate prescribing patterns and efficacy of prescribed monotherapy vs. polytherapy antihypertensive drugs in diabetes patients. A hospital-based prospective study was conducted in the medicine department of Kempegowda Institute of Medical Sciences Hospital and Research Center, Bangalore, India for a duration of 12 months. A total of 720 hypertensive patients with type 2 diabetes mellitus aged = 18 years were included in this study. Ninety patients (31%) were presented with chronic kidney disease, followed by ischemic heart disease (82, 28.3%), stroke (78, 26.9%), and heart failure (40, 13.8%). Monotherapy was prescribed more commonly than polytherapy (60.14% vs. 39.86%). The majority of patients were treated with Calcium channel blockers. In both therapeutic regimens, mono- and polytherapy, amlodipine was found to be the most prescribed drug. Comparison between results of antihypertensive monotherapy and polytherapy regimens (a combination of different classes of antihypertensive drugs) revealed that only prescription of polytherapy was associated with a statistically significant reduction in both systolic and diastolic blood pressure (mean (SD) of systolic blood pressure before polytherapy vs. after polytherapy; 166 (3.2) vs. 139 (1.4), < 0.0001. mean (SD) of diastolic blood pressure before polytherapy vs. after polytherapy; 103 (1.6) vs. 88 (0.5), < 0.0001). Systolic/diastolic blood pressure was not controlled and maintained within a therapeutic goal among patients who received single antihypertensive medication (monotherapy). Therefore, a combination of antihypertensive medications needs to be considered to achieve controlled blood pressure and avoid clinical inertia among hypertensive patients with diabetes.